Validity and reliability of rockport fitness walking test among students University Sains Malaysia Health Campus - Asari, Mohd Asnizam (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
Direct measurement of maximal oxygen uptake (V02max) has been well accepted as the most valid test for cardiorespiratory fitness. However, this method requires sophisticated and expensive laboratory equipment as well as trained personnel. It is also time consuming to test each participant individually and the participants themselves have to be physically exerted to obtain a true maximum for the results to be accurate. To overcome these practical problems, the Rockport Fitness Walking Test (RFWT), which is a less strenuous field test, has been used to estimate the V02max. The purpose of the present study was to test the validity and the reliability of the RFWT among the Malaysian students in the Health Campus, Universiti Sains Malaysia. Fifty healthy males (21.4 ± 1.6 year) and 50 healthy females (21.4 ± 1.6 year) recruited from the Health Campus, Universiti Sains Malaysia participated in this study. They performed one treadmill exercise test and two RFWT with the minimal of 4 days interval. The treadmill exercise test was conducted in a laboratory setting to determine the measured V02max that was used as the criterion value. The estimated V02max was obtained from the RFWT in an open field testing environment. The generalised equation of the Kline et al. (1987) was used for the calculation of the V02max. The correlation coefficient between the measured and estimated V02max values was r = 0.79 (p < 0.05). In terms of reliability, the RFWT has a high test-retest reliability (r = 0.92, p < 0.05). However, when the results were analysed separately according to gender, the correlation coefficient was 0.72 (p < 0.05) for the male participants and 0.31 (p < 0.05) for the female participants. The coefficient for the test-retest reliability was 0.91 (p < 0.05) and 0.77 (p < 0.05) for the male and female participants respectively. These results suggest that the RFWT is a valid and reliable field test for estimation of V02max among the male students. However, the RFWT tends to overpredict the actual V02max in the female students of Health Campus. Thus, the use of the RFWT on the female students to estimate their V02max should be treated with caution.